KONSEP PENGAWASAN DI LEMBAGA PENDIDIKAN DALAM PERSPEKTIF AL-QURAN DAN AL-HADIST - Yumawan, Restia Lasri; Sanusi, Hary Priatna (Prodi Ilmu Al-Qur'an dan Tafsir, 2023)
This study aims to examine the meaning of the concept of supervision in educational institutions according to the perspective of the Koran and al-Hadith. This research method is a qualitative research with a literature study approach. The data used in this study are in the form of document data, both from the Koran, al-Hadith, textbooks, scientific journals, and other relevant document sources. In terms of this literature study approach, the researcher looked for literature or literature data in the form of the concept of supervision in educational institutions according to the perspective of the Koran and al hadith. The results of the study show that Supervision is a point of view in an effort to control the progress of a plan in an organ to avoid a failure, whether fatal or not. In relation to this factor, the Qur'an provides a clear and unequivocal picture regarding things that are detrimental so that they do not happen. In line with the Koran, the hadiths of Rasulullah SAW also provide examples of behavior in the implementation of supervision in Islamic Education Institutions. The results of this study are expected to be used as a reference for educational practitioners, so that it has implications for the quality of education and overall educational goals.